Evaluation of Partial Factorization for Reduction of Finite Element Matrices - JARZĘBSKI, Pawel; WIŚNIEWSKI, Krzysztof (Engineering Transactions, 2017)
In this paper, we present the concept of Partial Factorization [1] And discuss its possible applications to the Finite Element method. We consider: (1) reduction of the element tangent matrix, which is particularly important for mixed/enhanced elements and (2) reduction of the sub-domain matrices of the Domain Decomposition (DD) equation solvers run either sequentially on a single machine or in parallel on a cluster of computers. We demonstrate that Partial Factorization can be beneficial for these applications.